2006
DOI: 10.1111/j.1365-2672.2005.02784.x
|View full text |Cite
|
Sign up to set email alerts
|

Which are the polyphosphate accumulating organisms in full-scale activated sludge enhanced biological phosphate removal systems in Australia?

Abstract: Aims:  To see if the compositions of the microbial communities in full scale enhanced biological phosphorus removal activated sludge systems were the same as those from laboratory scale sequencing batch reactors fed a synthetic sewage. Methods:  Biomass samples taken from nine full scale enhanced biological phosphate removal (EBPR) activated sludge plants in the eastern states of Australia were analysed for their populations of polyphosphate (polyP)‐accumulating organisms (PAO) using semi‐quantitative fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 44 publications
2
56
1
2
Order By: Relevance
“…Several reports have suggested that the Chloroflexi and type 0092 are frequent members of EBPR communities (7,8,24), although whether they play any role in phosphate removal in these communities is uncertain. None in samples taken at the end of the aerobic stage stained positively for polyP in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have suggested that the Chloroflexi and type 0092 are frequent members of EBPR communities (7,8,24), although whether they play any role in phosphate removal in these communities is uncertain. None in samples taken at the end of the aerobic stage stained positively for polyP in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In a laboratory-scale EBPR reactor fed propionate, Candidatus 'Accumulibacter phosphatis' occupied over 30% of the eubacterial population 18) . In addition, Candidatus 'Accumulibacter phosphatis' has also been found (4-18% of eubacteria) in full scale plants treating domestic sewage 24) and accumulated polyphosphate 5) . It is now regarded as one of the key PAOs species in EBPR processes 19) .…”
mentioning
confidence: 99%
“…Moreover, others speculated that Rhodocyclus-related PAOs (RPAOs) are an important PAO group in some EBPR processes 7,8) . On the other hand, Actinobacteria have also been found to be PAOs using clone libraries 14) , quinone profiling 21) , and FISH 3,28) . Liu et al indicated that some members of Actinobacteria composed one of the predominant groups of PAOs in a laboratory-scale EBPR process as determined by FISH with an Actino_1011 probe and 4',6'-diamidino-2-phenyl indol dihydrochloride staining 14) .…”
mentioning
confidence: 99%